2020
DOI: 10.3390/vetsci8010003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Histologic Grade of Digital Squamous Cell Carcinomas in Dogs with Dark and Light Haircoat—A Comparative Study of the Invasive Front and Tumor Cell Budding Systems

Abstract: Canine digital squamous cell carcinomas (CDSCC) are particularly aggressive when compared to their occurrence in other locations. Although these neoplasms are more frequently seen in dark-haired dogs, such as Giant Schnauzers, there are no data checking whether these tumors are histologically different between breeds. We histologically evaluated DSCC from 94 dogs. These were divided into two groups, namely, (1) dark-haired (N = 76) and (2) light-haired breeds (N = 18), further subdividing Group 1 into three su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…In the current retrospective multicenter study, 79 dogs with digital SCC were included. Based on our findings, we confirm that dark-coated dogs were over-represented similarly to earlier findings, with Schnauzers representing approximately one third of the population, further implicating a possible familial association and/ or genetic pre-disposition as previously described (12,16,17). Additionally, according to the univariate analysis, the Schnauzer breed was linked to a higher risk of tumor-specific death compared with all other breeds.…”
Section: Discussionsupporting
confidence: 90%
“…In the current retrospective multicenter study, 79 dogs with digital SCC were included. Based on our findings, we confirm that dark-coated dogs were over-represented similarly to earlier findings, with Schnauzers representing approximately one third of the population, further implicating a possible familial association and/ or genetic pre-disposition as previously described (12,16,17). Additionally, according to the univariate analysis, the Schnauzer breed was linked to a higher risk of tumor-specific death compared with all other breeds.…”
Section: Discussionsupporting
confidence: 90%
“…Hypothetically, if this copy number variation is also responsible for other predisposed breeds (e.g., Schnauzer) this must be investigated in further studies. Additionally, a previous study demonstrated that the digital SCC of dark-haired breeds had more histologically malignant features than their light-haired counterparts [ 26 ]. Nevertheless, this represents the first study identifying Jack Russell Terriers to have a significantly lower risk of developing digital SCC.…”
Section: Discussionmentioning
confidence: 99%
“…Amputation of the toe is the treatment of choice in dogs with dSCC [ 10 ]. The histological grade of malignancy can be assigned by two different systems adapted from human squamous cell carcinomas [ 11 , 12 ] to canine digital squamous cell carcinomas [ 13 ]. The risk of local recurrence can be considered low when resected in healthy tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Dark coat colour is correlated to the development and aggressiveness of squamous cell carcinoma [ 1 , 2 , 3 , 4 , 5 , 6 , 13 , 16 ]. A predisposition for squamous cell carcinoma in standard schnauzers (SS) and giant schnauzers (GS) has been identified by various authors [ 1 , 4 , 5 , 6 , 17 ].…”
Section: Introductionmentioning
confidence: 99%